Ethical considerations and legal issues relating to federated learning - CHIK, Warren B. (Institutional Knowledge at Singapore Management University, 2024)
In this chapter, we will explore the global trends and general principles relating to the ethics of federated learning systems. We will also examine the main legal issues relating to federated learning, in particular, the areas relating to the transparency and fairness of AI systems, privacy and personal data protection, intellectual property, legal ownership and rights to the system and output and governance concerns.